Motivation of Students from Universitas PGRI Yogyakarta in Participating in the Kampus Mengajar Program, 3rd Batch - Handayanti Handayanti; Rosalia Indriyati Saptatiningsih (AR-RUMMAN: Journal of Education and Learning Evaluation, 2024)
This research aims to analyze and describe the motivation of students from Universitas PGRI Yogyakarta in participating in the 3rd Batch of the Kampus Mengajar Program.This research is a descriptive qualitative study using the In-depth Interview method. Data sources were drawn from six informants, namely, the LKA UPY, the Target Schools for Placement of the 3rd Batch of Kampus Mengajar, and three student representatives from the 3rd Batch of Kampus Mengajar at Universitas PGRI Yogyakarta. All interview results were then reduced, data were displayed, and conclusions were drawn.The results of this study show that students from Universitas PGRI Yogyakarta are motivated to participate in the Kampus Mengajar Program because they will receive benefits such as: teaching experience to enhance teaching skills, expanding their network, obtaining 20 credits conversion, receiving monthly incentives and tuition fee waivers during the program, and obtaining a certificate to support their teaching career in the future. In addition to these benefits, students are also motivated to participate in Kampus Mengajar because they want to apply the knowledge gained in lectures to real-world situations.From this research, it can be used as a reference for follow-up actions related to motivating students to be interested in participating and increasing participation in the Kampus Mengajar program.